Analysis of the Leukocyte Profile for Peripheral Blood Smear Stained with Diff-Count Based on Fixation Time Variation - Museyaroh Museyaroh; Musholli Himmatun Nabilah; Lully Hanni Endarini (Knowledge Dynamics, 2025)
Background: Peripheral blood smear examination (HDT) is a test to observe the morphology of blood cells microscopically. A peripheral blood smear is a simple method, and its examination is widely available in laboratories. The advantage of peripheral blood smear examination is its ability to assess various components of peripheral blood cells, such as cell morphology (erythrocytes, leukocytes, and platelets). One of the commonly used methods for peripheral blood smear examination is Giemsa staining. The process of Giemsa staining fixation aims to preserve the cell structure and its components before the staining is performed. The precise fixation time is key to obtaining optimal staining results, which allows for accurate observation of cell morphology. The aim of this study is to analyze the morphology of leukocyte profiles in peripheral blood smears stained with Giemsa based on variations in fixation time to determine the optimal time. Methods: This research was conducted in August-September 2024. The sample in this study was whole blood taken from the academic community of the Department of Medical Laboratory Technology and examined with a peripheral blood smear using Giemsa staining, and analyzed using descriptive statistical tests with the SPSS for Windows 22 software. Results: The research results showed that at a fixation time of 3 minutes, 60% were good and 40% were less good; at 5 minutes, 100% were good; at 10 minutes, 100% were good; at 15 minutes, 40% were good and 60% were less good; and at 20 minutes, 20% were good and 80% were less good. Conclusion: The best time variation in Giemsa staining using phosphate buffer is fixation for 5 minutes and 10 minutes, where all preparations (5 preparations) are 100% in the good category.